Electronic structure and optical properties of N vacancy and O filling on n-GaN (0001) surface. (June 2018) - Lu, Feifei; Liu, Lei; Xia, Sihao; Diao, Yu; Feng, Shu
Abstract: In the X-ray photoelectron spectroscopy experiment, we observed that the valence band spectrum of the n-GaN (0001) surface appeared a bump near 1.9 eV after Ar etching and the N/Ga ratio became smaller, while the bump disappeared upon exposure to air. In order to analyze this phenomenon theoretically, we mainly study the electronic structure and optical properties of n-GaN (0001) surface with N vacancy and filled with O atom based on the first principles of density functional theory. The results suggest that the n-GaN (0001) surface exhibits semi-metallic property. The introduction of N vacancy reduces the n-type conductivity, whereas the filling of O atom enhances conductivity. The density of state near −1.9eV shows a good agreement between the clean n-type surface and the O-atom-filled surface, while the N vacancy surface has a higher density of states, which is similar to the experimentally observed phenomenon. It is also found that the existence of N vacancy reduces the photoemission properties of the n-GaN (0001) surface and the filling of O atom alleviates the defect caused by vacancy. This study shows that N vacancy increases the doping difficulty of n-type GaN films, however, the filling of O atom may compensate for the diminished photoelectric properties induced by N vacancy and be conducive to prepare high-performance optoelectronic devices with the contact of n-GaN and metal. Highlights: First principles is used for the interpretation of phenomenon observed in the X-ray photoelectron spectroscopy experiment. Simulation of N-vacancy and O-atom filling is on n-GaN (0001) surface. DOS induced by N vacancy is higher, while the DOS of O atom filled surface restore, which is in line with experiment datas. N vacancy is detrimental to the photoemission characteristics, whereas the filling of O atom may slightly alleviate.